INFLUENCE OF TEACHERS’ COMPETENCE ON SUCCESS OF SUNDAY-SCHOOL AS A MISSION FIELD AT AFRCAN INLAND CHURCH, BONDENI LOCAL CHURCH, KENYA - Rop, Charles; Ngige, John; Kithinji, Julius (International Journal of Research -GRANTHAALAYAH, 2021)
Sunday-school is an important component of the church because it helps the church to produce healthy individuals that become active members. The objective of the study was to examine the influence on teachers’ competence on the success of Sunday-school as a mission field at A.I.C Bondeni in Nakuru County, Kenya. Specifically, the study examined how budgetary allocation, competence of Sunday-school teachers and also how administrative support influence Sunday-school as a mission field in the aforementioned church. The population of 548 Sunday-school instructors, youth, parents of Sunday-school children, pastors, and administrators at the AIC Bondeni Local Church was studied using a descriptive survey design. Stratified random sampling was used to select 85 respondents from the research population. To obtain data, a detailed self-administered semi-structured questionnaire was used. The questionnaire was pilot tested before being used to collect data for the main study, in order to determine its validity and reliability. Prior to data collection, all necessary permits and consents were obtained. The collected data was analysed qualitatively and quantitatively with the aid of the Statistical Packages for Social Sciences software. Results revealed that teachers’ competence have a positive and statistically significant influence on the success of Sunday-school as a mission field. From the discoveries, the study recommends that AIC Bondeni and other churches should create budgetary allocation for teachers’ stipends, assess the theological understanding of Sunday-school teachers, and create continual teachers’ training and development programmes